A Case of Conjunctival Melanoma Presenting with Breast Metastasis - Canhoroz, Mustafa; Yogurt, Ismail; Gokgoz, Sahsuvar; Topal, Ugur; Kanat, Ozkan (Derman Medical Publ, 2015)
Most breast masses arise from the breast. Metastasis to the breast is fairly uncommon, but can occur in breast skin and parenchyma. In particular, leukemia and lung cancers, and MM may metastasize to the breast. Breast metastasis might be the first symptom or may occur during the course of other malignancies. Our case presented with a fixed mass in the upper-medial quadrant of her left breast during regular follow-up visits. The mean time to breast metastasis in patients with MM is 62 months (13-178). In our case this time was 48 months. In a case series with 7 patients hematological malignancies (Hodgkin lymphoma, non-Hodgkin lymphoma, and leukemia) were the leading cause of breast metastasis, whereas in only 1 case the cause was MM. In another case series of 15 MM patients with metastasis to the breast, the primary tumor was frequently localized to the upper extremities and trunk. In a report of 250 conjunctival MM cases the mortality rate was significantly higher in patients with tumors >4 mm in vertical thickness. In another 45-case MM series tumors with a diameter >10 mm were associated with higher mortality rates. In our case the thickness of the tumor was 5 mm. In conclusion, histopathological evaluation should be mandatory in patients with known primary malignancies in order to differentiate new primary tumors, metastases, and benign tumors.
Meme metastazı ile başvuran konjuktival melanom olgusu
Keywords: Malign Melanoma; Breast Metastasis; Conjuctival Melanoma